2004
DOI: 10.1007/s00244-003-2242-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient In Vitro Paraquat Removal via Irreversible Immobilization into Zeolite Particles

Abstract: A new efficient mineral adsorbent, zeolite ZSM-5, has been evaluated for its ability to durably immobilize the herbicide paraquat in conditions simulating acute poisoning by oral ingestion of this toxic compound. The sorption properties have been studied in water, normal saline solution, as well as in artificial and simulated human gastric juices. Uptake kinetics and capacities have been determined and compared to the ion exchange resin Amberlite IR-120. Significant advantages of ZSM-5 over the resin have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…'ZSM 5' zeolite (or MFI type, a synthesized zeolite), a hydrophobic solid, was found to adsorb atrazine better when organics were present in the zeolite' compartmentalized intra-crystalline void space [85,86]. ZSM-5 was found to accommodate paraquat herbicide in its microstructure with restricted mobility [87]; after this, Zhang et al (2006) [88] studied the release of paraquat from zeolites by ion exchange with 1.0 M Na + , and it was estimated to be 0.75 mmol g −1 of zeolite (14% by weight). Zeolites were also found to be slow-release carriers for 2,4-dichlorophenoxyacetic acid (2,4-D) herbicide [89,90].…”
Section: Slow Release Of Herbicidesmentioning
confidence: 99%
“…'ZSM 5' zeolite (or MFI type, a synthesized zeolite), a hydrophobic solid, was found to adsorb atrazine better when organics were present in the zeolite' compartmentalized intra-crystalline void space [85,86]. ZSM-5 was found to accommodate paraquat herbicide in its microstructure with restricted mobility [87]; after this, Zhang et al (2006) [88] studied the release of paraquat from zeolites by ion exchange with 1.0 M Na + , and it was estimated to be 0.75 mmol g −1 of zeolite (14% by weight). Zeolites were also found to be slow-release carriers for 2,4-dichlorophenoxyacetic acid (2,4-D) herbicide [89,90].…”
Section: Slow Release Of Herbicidesmentioning
confidence: 99%
“…Since there are no known pharmacological antagonists of paraquat and no chelating agents capable of binding the poison in the blood or other tissues, the management of paraquat poisoning has been directed towards the modification of the toxicokinetics of the poison by decreasing the absorption or decreasing the oxidant-induced cellular damage [11]. Zeolites have been evaluated by Walcarius and Mouchotte [12] for its ability to durably immobilize the paraquat in conditions simulating acute poisoning by oral ingestion of this toxic compound. Walcarius and Mouchotte [12] concluded that zeolites are promising primary treatment of acute paraquat poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites have been evaluated by Walcarius and Mouchotte [12] for its ability to durably immobilize the paraquat in conditions simulating acute poisoning by oral ingestion of this toxic compound. Walcarius and Mouchotte [12] concluded that zeolites are promising primary treatment of acute paraquat poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…: +81-78-441-7584; Fax:+ 81-78-441-7584; E-mail: a-adachi@kobepharma-u.ac.jp tivated carbon, zeolite particles, kaolinite, fuller's earth and bentonite have been evaluated for the treatment of acute pesticide poisoning by oral ingestion. [6][7][8][9] Because of the hydrophilic character of their surfaces, clay minerals, particularly phyllosilicates, have been shown to be very good adsorbents for highly polar pesticides, but their adsorption capacity for organic compounds is usually low. [10][11][12] Our research has focused on the adsorption properties of rice bran.…”
Section: Introductionmentioning
confidence: 99%